Effect Analysis of Practical Teaching Reform for Service Process of Low-temperature Orthosis - Xue ZHANG; Kaiyi QIU; Kuicheng LI; Xiaowei ZHANG; Jingming OUYANG; Minyi YE; Yuxing MO; Bei WANG (康复学报)
Objective:To explore the effect on the service flow of low-temperature orthosis in the modular practical teaching of rehabilitation technology.Methods:In the teaching course of low-temperature orthosis, 119 students of rehabilitation technology were randomly divided into observation group and control group, with 59 cases and 60 cases in each group. The control group was used the traditional teaching mode, the observation group was supplused standardized service flow of low-temperature orthosis based on the control group. At the end of the course, comparison of the students' theoretical and practical operation assessment scores between the two groups, and feedback on teaching effects through questionnaire.Results:The observation group students' theory and operation assessment scores were significantly better than the control group, with statistically significant differences (P<0.05).The questionnaire survey results showed that the average scores of the individual questionnaires and survey questionnaires of the observation group were higher than those of the control group, with statistically significant differences (P<0.05).Conclusion:In practice teaching of rehabilitation treatment technology, to standardize the application of the low-temperature orthosis service processmodular teaching gives better training outcome.